The Relationship Between Body Image, Self-Confidence, and Reproductive Health Among Adolescent Girls in Siak Regency in 2025 - Zuliyana, Zuliyana; Elektrina, Oktaliza; Okrianti, Surisna; Harahap, Amalia Dwi Oktami (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Body image and self-confidence are important psychosocial factors affecting adolescent girls’ reproductive health. Negative body image may influence self-esteem, reproductive health behavior, menstrual hygiene practices, and psychosocial well-being. This study aimed to analyze the relationship between body image and self-confidence with reproductive health among adolescent girls in Siak Regency in 2025. This study employed an analytic observational design with a cross-sectional approach. A total of 220 adolescent girls aged 15–19 years were selected using proportional random sampling techniques. Data were collected using validated questionnaires measuring body image, self-confidence, and reproductive health behaviors. Data analysis was conducted using the Chi-square test and multiple logistic regression analysis. The results demonstrated significant relationships between body image (p = 0.002) and self-confidence (p = 0.001) with reproductive health. Adolescent girls with a positive body image were 3.1 times more likely to exhibit good reproductive health behaviors, while those with high self-confidence were 2.8 times more likely. Body image was identified as the dominant factor associated with reproductive health. Therefore, strengthening adolescent counseling services and reproductive health education programs that integrate psychosocial aspects is highly recommended.